Recopilación de música tradicional ecuatoriana para coro mixto interpretada en la ciudad de Loja, durante los años 2015-2019. - Chamba Ávila, José Rolando (2022)
The main purpose of this research work was to compile the Ecuadorian traditional music for mixed choir performed in the city of Loja in the years 2015- 2019. In this way, the general objective was to strengthen the presence of traditional Ecuadorian music in the choral practice of the city of Loja. For this purpose, an interview was applied to 6 choir directors, which was conducted through the Zoom platform. A qualitative analysis of the answers of the different choirmasters was carried out. Likewise, with the information obtained, it was established that traditional Ecuadorian music is taken into account in its interpretation, however, the repertoire is limited in relation to the lack of variety of choral arrangements, which is why the interpretation of traditional works has been repetitive. On the other hand, it evidenced the lack of creation of new musical works for mixed choirs with traditional Ecuadorian repertoire. As a result, a compilation album of traditional Ecuadorian music for mixed choir was elaborated, which will help people who are immersed in the choral activity in the city of Loja. The methodology used during the research process was not directed to the experimental, for the reason that it is in the sociocultural field with descriptive tendency; interviews were applied, study of documents and the description of the facts that were presented in the course of the investigation. It is concluded that projects aimed at strengthening traditional Ecuadorian music are of utmost importance, in this case directed to the choral activity, the compilation of material for mixed choirs with traditional Ecuadorian music in the city of Loja. It is recommended to make memory of the ancestral music, it is significant the good experiences in the choral activity and in general in the musical field; the retrospective routines teach the human being to remember our roots; this will serve us to teach the future generations.